Dynamics of contact between Andean poetic production (Kichwa and A ymara) and the literar y canon - Rodríguez Monarca, Claudia (2017)
The article proposes to revise the dynamics of contact of the Andean indigenous poetic productions, both kichwa as aymara, with culture and the dominant national literatures and canonical of Ecuador and Bolivia, respectively. In these relationships we find interference of the dialog, more or less stressed, as the permeability, the confluence and divergence between literary systems.